DYNAMICS OF SUTTERBY NANOFLUID FLOW PAST A LINEARLY STRETCHING SHEET WITH SORET AND DUFOUR EFFECTS IN THE PRESENCE OF HOMOGENEOUS–HETEROGENEOUS REACTIONS - Muhammad Auwal, Danjuma; Usman, Auwalu Hamisu (FUDMA JOURNAL OF SCIENCES, 2026)
This paper investigates the effect of Dufour and Soret in the presence of homogeneous-heterogeneous reaction on the Sutterby nanofluid model over a stretching sheet. The problem of heat and mass transfer behavior of sutterby nanofluid a non-Newtonian fluid model represents dilute polymer solution which previously has not been treated together. The boundary layer partial differential equations are converted using appropriate transformations into ordinary differential equations. The homotopy analysis technique is used to solve nonlinear ordinary differential equations. The effects of various relevant parameters on velocity, temperature, and concentration profiles are graphically discussed. The behavior of the skin friction coefficient and the Nusselt number are also investigated.